Atomic scale observation of FCC twin, FCC → 9R and 9R → 12R' transformations in cold-rolled Hafnium. (15th January 2022) - Zhang, Yingdong; Li, Geping; Yuan, Fusen; Han, Fuzhou; Ali, Muhammad; Guo, Wenbin; Ren, Jie
Abstract: The face-centered cubic (FCC) twin, FCC →9R and 9R → 12R' transformations were observed simultaneously in cold-rolled pure Hf. The formation of FCC twin was due to the Shockley partial dislocations extended in the different basal planes. For FCC →9R transformation, the collective gliding of Shockley partial dislocations along (111) planes with every three atomic layers eventually lead to the stacking sequence of close-packed structure, i.e. ACBACBA CBA changed to ABACACB CBA. The 9R → 12R' transformation was related to the formation of the full dislocations at every three atomic layers. Graphical abstract: Image, graphical abstract